(untitled) (UUM Journal of Legal Studies, 2025)
Palm oil is the main product that has contributed significantly to the Indonesian and Malaysian economy over the past few decades. Oil palm plantations in Indonesia are owned not just by large corporations, but also by smallholders known as MSMEs (Micro, Small, and Medium Enterprises). One of the Indonesian government’s strategies to strengthen the capacity of MSMEs is to encourage large enterprises and MSMEs to form core-plasma partnerships. Large enterprises frequently incur various violations when implementing the palm oil industry partnership. As a result, adequate supervision from a government authority is essential. The purpose of this study is to examine the legal basis for the supervision of the Indonesian Competition Commission (‘ICC’; Komisi Pengawas Persaingan Usaha) on the implementation of core-plasma partnerships, to boost the oil palm plantation industry in Indonesia. This study type is normative-juridical and relies on secondary data sources to make assessments. The research typology used is analytical-descriptive, with the goal of fully and comprehensively explaining the duties and authorities of the ICC in supervising partnership implementation in Indonesia, and then evaluating them to determine the legal basis for the ICC’s participation in partnership implementation. The analysis found that Law No. 9 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition does not regulate the ICC’s authority to supervise partnerships. However, under Law No. 20 of 2008 on MSMEs and the implementation regulations, the ICC has the authority to oversee the implementation of core-plasma cooperation, namely through consultations, evaluations, suggestions, and considerations related to government policies, policy harmonization and law enforcement.